"Till debt do us part": financial implications of the divorce of the Irish Free State from the United Kingdom, 1922–1926. (22nd May 2020) - Fitzgerald, John; Kenny, Seán
Abstract: In this paper, we discuss the apportionment of national debt when Ireland exited the UK in 1922. We estimate that the claim on Ireland amounted to 80 percent of Irish Gross National Product (G.N.P.) and describe how it was ultimately waived at the expense of an unchanged land border with Northern Ireland. While this represents the largest debt relief episode in the twentieth century, the political cost of the agreement exceeded the financial gain in the long run. We find that domestic markets reacted more to political uncertainty than the pending liability, despite the financial stability which resulted from the debt write-down.